Towards Understanding the Roles of Heparan Sulfate Proteoglycans in Alzheimer's Disease - Zhang, Gan-lin (Hindawi Publishing Corporation, 2014)
Alzheimer's disease (AD) is the most common form of dementia, characterized by progressive loss of memory and cognitive dysfunctions. A central pathological event of AD is accumulation and deposition of cytotoxic amyloid-β peptide (Aβ) in the brain parenchyma. Heparan sulfate proteoglycans (HSPGs) and the side chains heparan sulfate (HS) are found associated with Aβ deposits in the brains of AD patients and transgenic animal models of AD. A growing body of evidence from in vitro and in vivo studies suggests functional roles of HSPG/HS in Aβ pathogenesis. Although the question of “how and why HSPG/HS is codeposited with Aβ?” still remains, it is within reach to understand the mechanisms of the events. Recent progress by immunohistochemical examination with advanced antibodies shed light on molecular structures of HS codeposited with Aβ. Several recent reports have provided important new insights into the roles of HSPG in Aβ pathogenesis. Particularly, experiments on mouse models revealed indispensible functions of HSPG in modulating Aβ-associated neuroinflammation and clearance of Aβ from the brain. Application of molecules to interfere with the interaction between HS and Aβ peptides has demonstrated beneficial effects on AD mouse models. Elucidating the functions of HSPG/HS in Aβ deposition and toxicity is leading to further understanding of the complex pathology of AD. The progress is encouraging development of new treatments for AD by targeting HS-Aβ interactions.